2016
DOI: 10.5897/ajb2015.15172
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate solubilization and multiple plant growth promoting properties of rhizobacteria isolated from chickpea (Cicer aeritinum L.) producing areas of Ethiopia

Abstract: Chickpea is one of the major legume crops widely grown in Ethiopia. The low availability of phosphorus in soil is among the stresses that constrain the production of this crop in the country. However, there are rhizobacteria capable of solubilizing insoluble forms of phosphorus in soil and make it available to the plant. Thus, this study was aimed at isolation and characterization of phosphate solubilizing bacteria from chickpea rhizosphere. Fifty phosphate solubilizing bacterial strains were isolated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…The phylogenetic tree was constructed using 16S rRNA sequence of the isolated strains with other genus and species of Enterobacter, Enterococcus, Kluyvera, Pantoea and Serratia forming four clades. Mulissa et al (2015Mulissa et al ( , 2016 reported the sequencing and clustering of E. cloacae, Enterobacter kobei, P. agglomerans and E. ludwigii from lentil rhizosphere all of which were identified in this study in the related grass pea rhizosphere. The sequences of the native isolates showed 30-99% similarity with each other and with sequences of related organisms obtained from NCBI forming four clusters, suggesting the existence of molecular diversity.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The phylogenetic tree was constructed using 16S rRNA sequence of the isolated strains with other genus and species of Enterobacter, Enterococcus, Kluyvera, Pantoea and Serratia forming four clades. Mulissa et al (2015Mulissa et al ( , 2016 reported the sequencing and clustering of E. cloacae, Enterobacter kobei, P. agglomerans and E. ludwigii from lentil rhizosphere all of which were identified in this study in the related grass pea rhizosphere. The sequences of the native isolates showed 30-99% similarity with each other and with sequences of related organisms obtained from NCBI forming four clusters, suggesting the existence of molecular diversity.…”
Section: Discussionmentioning
confidence: 60%
“…Rhizobacterial isolates screened from the rhizosphere of lentil and chickpea also produced solubilization indices of 1·34–2·25 cm and 1·44–3·06 cm, respectively (Mulissa et al . , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multifunctionality exhibited by R. leguminosarum makes it important in food production in terms of reducing cost and improving efficiency of P fertilization, especially in P-limited soils [14]. So far, phosphate solbilizing of fababean and chickpea nodulating rhizobial isolates from Ethiopian soils have been done by several authors [15], [16] and [17]. According to Feredegn [18] also assessed the phosphate solubilization of rhizosphere and endophytic bacteria from sugarcane (Saccharum officinarum L.).…”
Section: Introductionmentioning
confidence: 99%